A portable phonation duration meter having loudness level control / Syed Sahal Nazli Alhady Syed Hassan - Syed Hassan, Syed Sahal Nazli Alhady (1996)
In this project a portable phonation duration meter has been developed. This device is cheap and thus common people can effort to purchase it for their personal use. The device displays the duration of continuous phonation in second and stores it. Additional displays using LEDs have also been provided to indicate loudness level 'set' and the actual loudness of the phonation produced by the user. The device can be operated by 9V DC source and thus can be used in any condition.